(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
Background: Due to the internet’s recent rapid expansion, security has become a crucial issue when transmitting digital data via unsecure channels. This can be applied by employing dependable encryption methods. This research brought forward a text encryption system order to create safe databases. Materials and Methods: The research uses a chaotic map based on a logistic map Due to its widespread application in scientific research. Several processes are used to carry out the encryption activity. Firstly, the text is formatted in 2D matrix of numbers converted into vector. Secondly, to create a sequence for using it in the encryption process, the chaotic system is employed. Thirdly, sorting the generated vector in order to scramble the text values based on it. The final step involves encoding the scrambled text using a mathematical operation. Also, there are many steps used in the decryption process. In the first step, the same mathematical technique is used to decrypt the encrypted text after the identical chaotic sequence has been generated. In the second step, the scrambled values are descrambled to obtain the decrypted text. Results: The experimental results demonstrate that the suggested approach obtain an excellent value of entropy equal to (0.9955) and Correlation coefficient equal to (-0.0024) and Avalanche effect equal to (0.5120) as well as the proposed system examined under NIST tests and obtain a good results (>0.01) and examined for multiple other files and obtain a good results, in terms of execution time tests, the proposed system applied in a short amount of time. Conclusion: The proposed system matched the criteria for encryption techniques in terms of high sensitivity for initial values, high security, high randomizing Whatever text is to be encrypted. Also the proposed system can be applied for real time application due to its Short implementation time.